2007
DOI: 10.1016/j.exger.2006.10.002
|View full text |Cite
|
Sign up to set email alerts
|

A search for principles of disability using experimental impairment of Drosophila melanogaster

Abstract: The results of life table experiments to determine the effects of artificial impairment (leg amputation) in 7,500 D. melanogaster adults revealed that the extent to which life expectancy was reduced in impaired individuals was conditional on: (1) leg location and number amputated-front leg had greatest impact and the number of legs amputated directly correlated with mortality impact; (2) age of amputation-the greatest relative reduction in remaining life expectancy occurred when young flies were impaired; (3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 37 publications
(42 reference statements)
2
31
1
Order By: Relevance
“…These results partially corroborate Carey et al (2007), who found a stronger effect of injury on males than on females. However, we recorded mortality rates, while Carey et al (2007) recorded life expectancies, so the results are not directly comparable. Injury did not affect the rate of aging (i.e.…”
Section: Experiments 1: Injury Had a Significant Effect On Male Aging supporting
confidence: 88%
See 3 more Smart Citations
“…These results partially corroborate Carey et al (2007), who found a stronger effect of injury on males than on females. However, we recorded mortality rates, while Carey et al (2007) recorded life expectancies, so the results are not directly comparable. Injury did not affect the rate of aging (i.e.…”
Section: Experiments 1: Injury Had a Significant Effect On Male Aging supporting
confidence: 88%
“…However, these procedures resulted in acute effects on mortality, in that the flies died within the first few days, and sometimes within only the first few hours. We avoided removal of the front legs, which is a procedure that Carey et al (2007) included in their study, because of the role of the front legs in mating: males use the sex combs on their front legs to mount the female. We also avoided removal of the back legs in order to avoid a radical effect on the mobility of the injured flies.…”
Section: Experiments 1: Injury Had a Significant Effect On Male Aging mentioning
confidence: 99%
See 2 more Smart Citations
“…In primates, reported impairments include birth defects (Schultz 1956;Iwanoto 1967;Turner et al 2005), consequences of diseases like arthritis (Jurmain 2000;Nakai 2003) or aging (Randall 1944;Schultz 1944), as well as the results of injuries that are inflicted by external agents and accidents (Jurmain 1989(Jurmain , 1997Lovell 1990). Only when impairments hamper essential activities do they cause disability (Byrne and Stokes 2002;Carey et al 2007). …”
Section: Introductionmentioning
confidence: 99%